ASPEK HUKUM TENTANG REKLAMASI PERTAMBANGAN BATUBARA STUDI DI KECAMATAN SATUI TANAH BUMBU - Suprapto Suprapto (Fakultas Hukum, Universitas Islam Bandung, 2011)
Coal mining on the one hand bring benefits in terms of economics, but on the other hand can cause a variety of environmental problems, one of which caused the rise of mining without a permit in scattered districts in South Borneo, one of them in the Land of Spices, especially Sub District Satui. This research is a normative juridical research. Function of law in the field of environmental conservation is a social enginering. In this field are expected to create a behavior that is oriented to the preservation of the environment, natural resources and ecosystems for the benefit of present and future. Based on Law Number 4 Year 2009 on mineral and coal mining, reclamation place, as one of the obligations of the company's Mining Permit holders.